2016
DOI: 10.1111/dom.12735
|View full text |Cite
|
Sign up to set email alerts
|

Robust anti‐obesity and metabolic effects of a dual GLP‐1/glucagon receptor peptide agonist in rodents and non‐human primates

Abstract: AimsTo characterize the pharmacology of MEDI0382, a peptide dual agonist of glucagon‐like peptide‐1 (GLP‐1) and glucagon receptors.Materials and methods MEDI0382 was evaluated in vitro for its ability to stimulate cAMP accumulation in cell lines expressing transfected recombinant or endogenous GLP‐1 or glucagon receptors, to potentiate glucose‐stimulated insulin secretion (GSIS) in pancreatic β‐cell lines and stimulate hepatic glucose output (HGO) by primary hepatocytes. The ability of MEDI0382 to reduce body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(175 citation statements)
references
References 44 publications
8
158
0
1
Order By: Relevance
“…To a lesser magnitude relative to what was observed in obese wild-type mice, the dual agonist also lowered body weight in mice lacking the GLP-1 receptor, thus corroborating that GcgR agonism is a valuable constituent to the combined pharmacology (Day et al, 2009). Of appreciable note, GLP-1/ glucagon dual agonism also effectively lowers body weight and improves glycemia in nonhuman primates (Tschop et al, 2016), an important observation later also confirmed with another GLP-1/glucagon dual agonist (Henderson et al, 2016). Another interesting and unexpected finding was the ability of such a dual agonist to improve leptin sensitivity of DIO mice, despite continued chronic exposure of the mice to a high-sugar HFD .…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 69%
See 2 more Smart Citations
“…To a lesser magnitude relative to what was observed in obese wild-type mice, the dual agonist also lowered body weight in mice lacking the GLP-1 receptor, thus corroborating that GcgR agonism is a valuable constituent to the combined pharmacology (Day et al, 2009). Of appreciable note, GLP-1/ glucagon dual agonism also effectively lowers body weight and improves glycemia in nonhuman primates (Tschop et al, 2016), an important observation later also confirmed with another GLP-1/glucagon dual agonist (Henderson et al, 2016). Another interesting and unexpected finding was the ability of such a dual agonist to improve leptin sensitivity of DIO mice, despite continued chronic exposure of the mice to a high-sugar HFD .…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 69%
“…The initial 2009 coagonist report was received with healthy scientific skepticism, but the independent confirmation at other research sites and the translation from obese rodents to nonhuman primates have supported the advancement of the concept to human studies (Day et al, 2009Pocai et al, 2009;Henderson et al, 2016). Separately, low-dose coinfusion of GLP-1 and glucagon has been demonstrated to decrease food intake (Cegla et al, 2014) and to increase energy expenditure in humans (Tan et al, 2013).…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Lao et al reported that their dual GLP‐1R/GCGR agonist showed higher weight loss in diet‐induced obese rhesus monkeys and better glucose control in diabetic rhesus monkeys than GLP‐1R agonist gold standard liraglutide . A recent report also indicates that administration of MEDI0382, a dual GLP‐1R/GCGR agonist, at toxicological doses, to lean and healthy cynomolgus monkeys led to significant reduction in body weight . The impact on body weight results from a significant suppression of energy intake but may also arise from increased energy expenditure as observed in a sub‐chronic study in rats, in a multiple dosing study for 4 weeks in DIO mice and in humans .…”
Section: Introductionmentioning
confidence: 96%
“…Recently, several GLP‐1/GR dual agonists have been under development (Table ). Preclinical studies showed that the GLP‐1R/GR dual agonist, SAR425899 (Sanofi, Paris, France), decreased bodyweight in diet‐induced obese mice and ameliorated glucose levels in db / db mice, and that the GLP‐1R/GR dual agonist, MEDI0382 (MedImmune, Gaithersburg, MD, USA), significantly reduced bodyweight and improved glucose tolerance to levels similar to those obtained by the GLP‐1R agonist, liraglutide, in non‐human primates. Based on the promising results with GLP‐1R/GIPR and GLP‐1R/GR dual agonists, GLP‐1R/GIPR/GR triple agonists also have been under development as therapeutics for type 2 diabetes (Table ).…”
Section: List Of Antidiabetic Drugs Targeting Glucagon‐like Peptide‐1mentioning
confidence: 96%